Assessment of the best representative concentration pathways (RCPs) for northern Malaysia - Fatin Nabila, Abllah (2019)
Consequence from the climate change in Malaysia had leads to flood disaster in Perlis that happened in year 2010 that involved 50 000 victims need to evacuate from their house to temporary settlement areas besides caused death of 6 victims. Thus, the climate prediction in the future year become necessary in planning and managing the water resources and disasters prevention. However the main issue in the long term climate prediction was the appropriate level radiation of the local region which presented in the Representative Concentration Pathways (RCPs). The RCP has been introduced by Coupled Model Intercomparison Project Phase 5 (CMIP5) and presented in three radiation levels known as RCP2.6, RCP4.5 and RCP8.5. Every RCP had its own specific emissions trajectory and subsequent radiative forcing in altering the balance of incoming and outgoing energy into the Earth system. It considers the total radiative forcing until year 2100. Therefore, the objective of this study was to identify the best RCPs for the Northern Malaysia (Perlis and Pulau Pinang) and to generate the long term climate trend at these regions. Based on the results, there were 5 predictors which the most been selected ; ncepr850, nceptemp,nceprhum,ncepr500 and ncepp500. The calibrated and validated results shows the RCP2.6 was the best to present the radiation forcing level at Northern state with very low percentage error which 0.208% and correlation closed to 1. The projected climate revealed the temperature is expected to increase in the future year and reaches 35˚C with 0.01% increment. Besides that, May is expected as the month which receiving the highest temperature through the year. Meanwhile, the rainfall is estimated to reduce 7.2% (2020), 12% (2050) and 15% (2080).